AGRICULTURE-BASED TOURISM VILLAGE DEVELOPMENT STRATEGY AND THE ROLE OF AGRICULTURAL EXTENTION WORKERS IN SUKOMAKMUR - Fatikhah Nurul Fajri; Pramesti Megayana (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study investigates the development strategy of an agriculture-based tourism village and the role of agricultural extension workers in Sukomakmur, Kajoran, Magelang. The research employed Internal Factor Evaluation (IFE), External Factor Evaluation (EFE), the Internal–External (IE) matrix, SWOT analysis, and the Quantitative Strategic Planning Matrix (QSPM) to formulate and prioritize strategies. Results of IFE and EFE indicate that strengths such as village regulation, natural potential, active farmer and tourism groups, proactive extension workers, and preserved local wisdom outweigh weaknesses, while opportunities from digital promotion, tourism market expansion, and stakeholder support are greater than threats such as climate risks, competition, and changing trends. The IE matrix positioned Sukomakmur in the growth and build quadrant, showing strong internal capacity and external opportunities. SWOT and QSPM analyses highlighted WO1 (utilizing stakeholder support to increase capital and infrastructure) and SO1 (optimizing digital promotion of natural landscapes) as the most prioritized strategies, followed by ST1 (assisting farmers in mitigating crop failure risks) and WT2 (developing SOPs to protect agricultural land from tourism impacts). The findings emphasize the pivotal role of agricultural extension workers as facilitators, mentors, and mediators in empowering local communities, strengthening institutional collaboration, and ensuring the sustainability and competitiveness of agrotourism development.